2006
DOI: 10.1016/j.dnarep.2006.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel motif in DNA ligases exemplified by DNA ligase IV

Abstract: Penny (2006) Identification of a novel motif in DNA ligases exemplified by DNA ligase IV. DNA Repair, 5 (7). pp. 788-798. ISSN 1568-7864 This version is available from Sussex Research Online: http://sro.sussex.ac.uk/17805/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Other ligases are capable of DNA recognition regardless of adenylation status. Recombinant ligase IV/XRCC4 exhibits a weak DNA-binding activity on short DNA substrates and it has been reported that formation of the ligase IV-adenylate is necessary for Ku-mediated binding of recombinant ligase IV/XRCC4 to short DNA substrates (47,48). Along these lines, we found that XRCC4 in cell line 180BRM, which expresses a mutant ligase IV with reduced ability to form the ligase IV-adenylate, fails to bind DNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Other ligases are capable of DNA recognition regardless of adenylation status. Recombinant ligase IV/XRCC4 exhibits a weak DNA-binding activity on short DNA substrates and it has been reported that formation of the ligase IV-adenylate is necessary for Ku-mediated binding of recombinant ligase IV/XRCC4 to short DNA substrates (47,48). Along these lines, we found that XRCC4 in cell line 180BRM, which expresses a mutant ligase IV with reduced ability to form the ligase IV-adenylate, fails to bind DNA (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Several assays can measure and quantify cellular responses to DNA double-strand breaks. The proteins, such as c-H2AX, ATM, CDKN1A, and TP53, involved in the early steps of the cellular response in sensing DNA damage and controlling progression, have been proposed as the top group of candidate biomarkers (Marchetti et al, 2006). Due to the signal amplification of c-H2AX foci at the site of DNA damage, the detection of c-H2AX has been identified as an early sensitive cellular biomarker of DNA damage (Nikolova et al, 2014;Rogakou et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Since the ATP-binding pocket lies between the subdomains, it is likely that M249V, R278H, Q280R and H282L lead to instability or conformational change in the ATP-binding pocket, resulting in a large reduction of the adenylation efficiency as reported for R278H [149]. G469, a residue in motif Va, which is important for the adenylation of LigIV [103], is completely buried and surrounded by large hydrophobic residues. Therefore, it is likely that G469E leads to disruption of the conformation of OBD.…”
Section: Nhej Deficiencymentioning
confidence: 96%